The Events and Their Types in Geodetic Measurements - Juraeva Husnora Davronovna; Yuldashev Akmal Olimovich (Peerian Journals Publishing, 2022)
We all know that the main part of geodetic work is measurements with geodetic instruments. As a result of measurements, numerical values are obtained, and numerical values are repeatedly measured in geodesy. To improve the quality of the measurement, in addition to the necessary values, excess values are also measured. It is carried out due to the presence of excess measurements, due to measurement errors. The presence of measurement errors forces us to carry out additional measurements and resort to probability theory.
Keywords: random variables; their distribution laws; numerical characteristics; random event